Bergamot (Citrus bergamia) leaf extract improves metabolic, antioxidant and anti-inflammatory activity in skeletal muscles in a metabolic syndrome experimental model - Palacio, Thiago Luiz Novaga [UNESP]; Siqueira, Juliana Silva [UNESP]; de Paula, Bruno Henrique [UNESP]; Rego, Rebeca Mayara Padilha [UNESP]; Vieira, Taynara Aparecida [UNESP]; Baron, Giovanna; Altomare, Alessandra; Ferron, Artur Junio Togneri [UNESP]; Aldini, Giancarlo; Kano, Hugo Tadashi [UNESP]; Correa, Camila Renata [UNESP] (Taylor & Francis, 2023)
Metabolic Syndrome (MetS), inflammation and oxidative stress contribute to impairment of skeletal muscle function. Bergamot (Citrus bergamia) leaf extract (BLE) has shown protective effects against comorbidities associated with MetS through its anti-inflammatory and antioxidant effects. The aim of this work was to elucidate the antioxidant and anti-inflammatory activity of BLE in skeletal muscles in an experimental model of MetS. Once metabolic syndrome was diagnosed, animals were divided into groups receiving different treatments for 10 weeks, including control diet (n = 10), control + BLE (n = 10), High Sugar-fat diet (HSF) (n = 10), HSF + BLE (n = 10). Evaluation included nutritional, metabolic and hormonal analyses, along with measurements of inflammatory status and oxidative stress in soleus and extensor digitorum longus (EDL) muscles. BLE showed positive metabolic effects, with a reduction of plasma triglycerides and insulin resistance and an increase in high-density lipoprotein cholesterol, and protective activity against oxidative stress and inflammation in Soleus and EDL muscles in animals with MetS.
Keywords: bioactive compounds; inflammation; Metabolic syndrome; oxidative stress